2020
DOI: 10.1186/s12920-020-00789-8
|View full text |Cite
|
Sign up to set email alerts
|

Multiple paragangliomas: a case report

Abstract: Background Carotid and vagal paragangliomas (CPGLs and VPGLs) are rare neoplasms that arise from the paraganglia located at the bifurcation of carotid arteries and vagal trunk, respectively. Both tumors can occur jointly as multiple paragangliomas accounting for approximately 10 to 20% of all head and neck paragangliomas. However, molecular and genetic mechanisms underlying the pathogenesis of multiple paragangliomas remain elusive. Case presentation We report a case of multiple paragangliomas in a patient, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…We conclude this special journal issue by the multiple paraganglioma cases report compiled by Vladislav Pavlov et al [21] (this issue). The authors report a case of multiple paragangliomas, manifesting as bilateral carotid and vagal paragangliomas.…”
mentioning
confidence: 69%
“…We conclude this special journal issue by the multiple paraganglioma cases report compiled by Vladislav Pavlov et al [21] (this issue). The authors report a case of multiple paragangliomas, manifesting as bilateral carotid and vagal paragangliomas.…”
mentioning
confidence: 69%
“…However, Petri et al reported opposite results; it was shown that despite the loss of the p53 locus on 17p in many benign and metastasizing PHEOs, no mutations or rare positive nuclear protein immunostaining were identified in association with metastatic disease [96]. Several cases reported TP53 mutations occurring together with pathogenic variants in other susceptibility genes in a multiple HNPGL (TP53 and SDHD) [98] and a metastasizing PHEO (TP53 and SDHB) [99]. In addition, a recent study revealed an antitumor effect of wild-type TP53 upregulation in PC12 cells through the induction of cell cycle arrest and apoptosis [100].…”
Section: Mutations and Dna Methylationmentioning
confidence: 99%